78 Effects of strategic supplementation of low quality diets and previously determined residual feed intake rank on performance in gestating beef cattle. (7th December 2018) - Devos, J; Campbell, C; Wood, K; Schenkel, F; Mandell, I
Abstract: A two-year wintering beef cow study was conducted evaluating effects of strategic supplementation of straw-based diets with an energy-protein supplement fed over the last 75 days of gestation on cow and pre-weaning calf performance. Residual feed intake (RFI) ranks from the 2015 gestation period (RFI2015) were compared to RFI determined in 2016 and 2017 using intraclass correlations and Spearman correlation coefficients. Gestating crossbred beef cows (n = 116, 141 ± 18 days in gestation, 672.6 ± 99.2 kg BW) were allocated to one of five nutritional regimens (NR): 1) 70% haylage, 30% millet straw on a dry matter basis (DMB) fed ad libitum (HAYL), 2) straw fed ad libitum along with haylage at 0.8% DMB of cow BW (MSHAYL), 3) MSHAYL along with energy-protein supplement once/week, 4) twice/week, or 5) three times/week. Supplement contained 54.6% corn gluten meal and 23.4% SBM, and 21.0% calcium propionate, fed at 0.32 g/kg BW per day (DMB). Cows were evaluated during 22015 values were ranked into quartiles; 12015 rankings. HAYL cows had greater (P < 0.001) gestation DMI, ADG, and fat deposition. No effects (P > 0.05) for supplementation or supplementation frequency were found except that supplementation increased (P = 0.016) DMI. RFI2015 rank was not repeatable (R = 0.06, P > 0.48), nor correlated to RFI rank measures found during 2016 (r = -0.03, P > 0.76) or 2017 (r = 0.23, P < 0.06). Both NR and year affected (P < 0.001) reranking between years. Overall, RFI ranks measured during 2015 were not repeatable between years and were affected by NR. Wintering cow performance was related to NR.